EFEKTIFITAS PENERAPAN MANAJEMEN PERPUSTAKAAN MENGGUNAKAN SENAYAN LIBRARY MANAJEMEN SISTEM (SLIMS) PADA PERPUSTAKAAN UNIVERSITAS INDONESIA TIMUR. - Harianto; Fatri Ardiansyah; Indra Setya Permana; Sukarman (Literatify: Trends in Library Developments, 2024)
This research aims to evaluate the effectiveness of implementing library management using Senayan Library Management (SLIMS) at the University of East Indonesia Library, with a focus on the application of information technology to improve service efficiency and library information access. The research method used is descriptive qualitative with a phenomenological approach, exploring experiences and phenomena related to service mechanisms and information processing in the library. Data was collected through direct observation and in-depth interviews with library heads, librarians and users. Data analysis involves collecting, reducing, assessing, and critically interpreting data to reach conclusions. The implementation of SLIMS in libraries has had a positive impact, increasing operational efficiency with easy access via online OPAC, bibliographic management and fast E-Library membership. Despite progress, integration of SLIMS with other technologies such as online access to e-journal and e-book collections is still in the preparation stage. Constraining factors involve data availability, metadata standards, security and access, changes in digital resources, identity management, resource availability, and alignment with user needs which are still being adapted.